Laparoscopic findings of infertile women at Bangabandhu Sheikh Mujib Medical University - Ishrat, Shakeela; Deeba, Farzana; Banu, Jesmine; Diti, Afruna Rahman (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Laparoscopy is an important component of infertility work up. It is the gold standard for evaluation of pelvic pathology and assessment of tubal patency. Objective: The objective of the study was to analyze the laparoscopic findings of infertile women presenting at Infertlity unit of Bangabandhu Sheikh Mujib Medical University. Method: We had a retrospective cross-sectional study on Japaroscopic findings of 110 women. Results: Out of all patients 22.7% women had endometriosis. Various degrees of adhesion of pouch of Douglus was present in 16.4 %. Regarding tubal pate:1cy , 26.4% had unilateral block and 28.2% had bilateral block. Conclusion: A significant number of infertile women at the Infertility unit of BSMMU has tuboperitoneal disease and bilateral tubal block and ultimately need in vitro fertilization.